New emissions inventory for Athens and its use to improve air quality predictions - Toll, Isabel; Moussiopoulos, Nicolas S.; Sahm, Peter; Samaras, Zissis; Aslanoglou, Miltos; Zachariadis, Theodoros (My University, 1995)
Aim of this paper is to describe the methodology followed to create a new emissions inventory for the Greater Athens area in 1990 and the results of its application as input to the photochemical dispersion model MARS. The sources considered are anthropogenic ones: traffic, domestic heating, industry and fuel storage. Emissions coming from road traffic, which is the most important source of air pollution in Athens, are calculated with a microscale methodology using the CORINAIR/COPERT emission factors. The EUMAC Zooming Model (EZM) is applied for May 25, 1990 using alternatively the new and an older version of the emissions inventory. The comparison of the model results reveals that the new inventory allows achieving a better agreement between model results and observations, especially as far as species of low reactivity are concerned.